(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The study aimed to identify the effect of pineapple hump extracts in different doses on increasing the chemical and physical quality of rabbit meat. Materials and Methods: The research stages were carried out with maintenance for two months using a completely randomized design consisting of four treatments and five replicates. P0 = complete ration without pineapple hump extract; P1 = complete ration with the addition of 0.2% pineapple hump extract; P2 = complete ration with the addition of 0.4% pineapple hump extract; and P3 = complete ration with the addition of 0.6% pineapple hump extract. The variables observed were the chemical quality of meat (pH, moisture, carbohydrate, fat, and protein content in rabbit meat), and the physical quality (water holding capacity (WHC), cooking loss). Results: The data were analyzed using SAS, with significantly different results subjected to Duncan’s further testing. The addition of 0.4% pineapple hump extract in rabbit complete rations had a very significant effect on the WHC of 71.62%. The addition of 0.6% pineapple hump extract also had a significant effect on the protein content of meat, increasing it by 19.17%. Conclusion: The effects of pineapple hump extract up to 0.6% in a complete diet of weaned rabbits have a positive effect on the physical and chemical quality of rabbit meat, especially on the protein and water-holding capacity of rabbit meat. Adv. Vet. Anim. Res., 11(2): 296-301, June 2024 http://doi.org/10.5455/javar.2024.k776